The Role of Family in Schizophrenia Relapse Reflected in ‘Everything Here Is Beautiful’ - Tegar, Firza; Thohiriyah, Thohiriyah (Universitas Muhammadiyah Barru, 2025)
Everything Here is beautiful is a novel by Mira T. Lee, which potrays Lucia, a Chinese – American who struggles with schizophrenia. Through this novel, Mira T. Lee vividly potray the immense struggle of living with schizophrenia and the challenges of leading an everyday life. Schizophrenia is a complex mental disorder that requires the family's role in providing support and treatment. By using Sigmund Freud's theory of the unconscious mind, this study aims to emphasize the crucial role of family dynamics in shaping the condition of individuals with schizophrenia. The article employs a qualitative approach to conduct an in-depth analysis of the dynamics of the id, Ego, and Superego in order to reveal the relapse of the schizophrenia condition experienced by Lucia. The findings show that dysfunctional family dynamics can trigger an identity crisis, which in turn exacerbates schizophrenia symptoms such as hallucinations, delusions, abnormal behavior, disorganized thinking, and emotional disturbances. The study provides a novel perspective on familial impact through literary character analysis.